First Report on the Plasmidome From a High-Altitude Lake of the Andean Puna - Perez, María Florencia; Kurth, Daniel; Farías, María Eugenia; Soria, Mariana Noelia; Castillo Villamizar, Genis Andrés; Poehlein, Anja; Daniel, Rolf; Dib, Julián Rafael (Frontiers in Microbiology, 2020)
Mobile genetic elements, including plasmids, drive the evolution of prokaryotic genomes through the horizontal transfer of genes allowing genetic exchange between bacteria. Moreover, plasmids carry accessory genes, which encode functions that may offer an advantage to the host. Thus, it is expected that in a certain ecological niche, plasmids are enriched in accessory functions, which are important for their hosts to proliferate in that niche. Puquio de Campo Naranja is a high-altitude lake from the Andean Puna exposed to multiple extreme conditions, including high UV radiation, alkalinity, high concentrations of arsenic, heavy metals, dissolved salts, high thermal amplitude and low O2 pressure. Microorganisms living in this lake need to develop efficient mechanisms and strategies to cope under these conditions. The aim of this study was to characterize the plasmidome of microbialites from Puquio de Campo Naranja, and identify potential hosts and encoded functions using a deep-sequencing approach. The potential ecological impact of the plasmidome, including plasmids from cultivable and non-cultivable microorganisms, is described for the first time in a lake representing an extreme environment of the Puna. This study showed that the recovered genetic information for the plasmidome was novel in comparison to the metagenome derived from the same environment. The study of the total plasmid population allowed the identification of genetic features typically encoded by plasmids, such as resistance and virulence factors. The resistance genes comprised resistances to heavy metals, antibiotics and stress factors. These results highlight the key role of plasmids for their hosts and impact of extrachromosomal elements to thrive in a certain ecological niche.